2013
DOI: 10.1111/tbed.12129
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk of African Swine Fever Introduction into the European Union by Wild Boar

Abstract: The presence of African swine fever (ASF) in the Caucasus region and Russian Federation has increased concerns that wild boars may introduce the ASF virus into the European Union (EU). This study describes a semi-quantitative approach for evaluating the risk of ASF introduction into the EU by wild boar movements based on the following risk estimators: the susceptible population of (1) wild boars and (2) domestic pigs in the country of origin; the outbreak density in (3) wild boars and (4) domestic pigs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 25 publications
2
96
0
2
Order By: Relevance
“…In the Baltic countries and in Poland, it was observed that wild boar habitat suitability, neighbouring distance from infected wild boar and domestic pigs were the main risk factors for the introduction into EU free areas through infected wild boar [39]. Different studies highlighted the continuity of the geographical distribution of wild boar, wild boar management (hunting system, winter feeding), local density and size of the infected population, direct contact with dead infected wild boar, as the most relevant risks for the spread and the persistence of the virus in wild boar populations [4, 25, 40].…”
Section: Reviewmentioning
confidence: 99%
“…In the Baltic countries and in Poland, it was observed that wild boar habitat suitability, neighbouring distance from infected wild boar and domestic pigs were the main risk factors for the introduction into EU free areas through infected wild boar [39]. Different studies highlighted the continuity of the geographical distribution of wild boar, wild boar management (hunting system, winter feeding), local density and size of the infected population, direct contact with dead infected wild boar, as the most relevant risks for the spread and the persistence of the virus in wild boar populations [4, 25, 40].…”
Section: Reviewmentioning
confidence: 99%
“…In the case of the Iberian Peninsula, Bosch et al (2012) have recently created a habitat suitability map for wild boar based on the availability of vegetation resources, i.e., food resources and shelter. These authors used different studies to assess the risk of introducing disease along vegetation corridors crossing national borders (De la Torre et al, 2013). Furthermore, these studies also have been applied in Spanish epidemiological surveillance programs for certain diseases (Ministerio de Agricultura, Alimentación y Medio Ambiente, Spain, 2013).…”
mentioning
confidence: 99%
“…The risk of introduction of ASFV by wild boar into the European Union as estimated after the outbreaks in the Caucasus region and Russian Federation concerns mostly Finland, Romania, Latvia and Poland and not Greece for the moment (De la Torre et al 2013). Although ASF is not a zoonotic disease, surveillance to timely identify isolates and prevent spreading of the disease is of great importance given the absence of an effective vaccine available or any effective treatment.…”
Section: Discussionmentioning
confidence: 99%